The inevitable fallibility of policing - Newburn, Tim (Policing and society, 2022)
The title of this paper is taken from the final sentence of the book How People Judge Policing (Waddington et al. [2017]. How People Judge Policing. Oxford: Oxford University Press.) which, though it had four authors, was really the brainchild of the late Tank Waddington. The paper picks up the book’s final observation and seeks to develop it, examining the problematic core of policing, and using this as a basis for thinking more generally about issues of trust, legitimacy and reform. There now exists an increasing body of research which shows how the delivery of policing can influence perceived procedural justice, the popular legitimacy of the police, and a variety of public behaviours such as compliance with the law and co-operation with the police (Tyler, [2017] Procedural justice and policing: A rush to judgement? Annual Review of Law and Social Science, 13, 29–53.). Such work is having increased impact on debates around police conduct and legitimacy and is increasingly seen as central to police reform efforts in Anglo-American policing, and in some other jurisdictions. Though accepting the broad thrust of such research, as well as its importance, this paper suggests that there are dangers in over-reading the potential of procedural justice, not least in forgetting some crucial lessons from the history of police research. The argument here focuses on the inherent complexity of policing and the inevitability of error within it. The simple but often overlooked lesson is that controversy and dissent are the norm rather than the exception in policing, and that much dispute and disagreement rather than reflecting a failure of approach or procedure, derive from the nature of policing itself.